“Efecto de la aplicación de cuatro dosis de materia orgánica (gallinaza) en el cultivo de col china (brassica pakinensis) híbrido kiboho 90 F-1, en el distrito de Lamas” - Cubas Zamora, Teobaldo (2016)
This research aims to evaluate the dose greater effect of organic matter (manure) on performance and conduct economic analysis of the treatments in the cultivation of Chinese cabbage (Brassica rapa pekinensis) Hybrid Kiboho 90 F- 1 under the ecological conditions in the district of Lamas. The research was conducted on the grounds of Fundo Pacific owned by Mr. Jorge Luis Pelaez Rivera, located in the district and province of Lamas, San Martin department. The statistical design of randomized complete block design (RCBD) with four blocks and five treatments was used, making a total of 20 experimental units. Field information obtained was processed with statistical program SPSS 19, which uses the P-value as comparator significant differences confidence levels of 0.05 and 0.01 in the analysis of variance (ANOVA) and multiple range test of Duncan P